Embedding the Safe System into the next generation of road safety audits - Michael de Roos (19774392) (2015)
Road Safety Audits are used to identify risks and to propose remedial works on new and existing. The Safe System requires a change in focus from mitigating crashes to preventing death and serious injury. Development of the Qatar Road Safety Audit Guide (RSAG) presented an ideal opportunity to reinvigorate road safety auditing practices in accordance with the Safe System. The Public Works Authority (Ashghal) commissioned a RSAG that was to be suitable for Qatar operating environment and based on leading international practices. The Qatar National Road Safety Strategy adopts the Safe System as the model for developing and delivering road safety initiatives, it followed that the RSAG follow the same principles. This was also in accordance with the United Nations: Decade of Action for Road Safety initiative. The RSAG adopts the survivability graph (Wramborg quoted in OECD, 2008) to rank seriousness of deficiencies identified. This allows us to focus on delivering the greatest road safety benefits. Traditional checklists used in road safety audits have been revised to include the possibility of a a head-on crash at 70 km/h, a side-impact crash at 50 km/h, collide with a non-frangible object at 40 km/h or hit a pedestrian at 30 km/h. If the answer is yes to any of these questions there is a need to take action. The Safe System is progressively being implemented globally as a new approach to reducing the unacceptable number of people being killed or injured. The Qatar Road Safety Audit Guide has successfully demonstrated that the Safe System can be integrated into road safety auditing practices. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.20